Evolution and biomineralization of pteropod shells - Ramos-Silva, P.; Wall-Palmer, D.; Marlétaz, F.; Marin, F.; Peijnenburg, K.T.C.A. (Journal of Structural Biology, 2021)
Shelled pteropods, known as sea butterflies, are a group of small gastropods that spend their entire lives swimming and drifting in the open ocean. They build thin shells of aragonite, a metastable polymorph of calcium carbonate. Pteropod shells have been shown to experience dissolution and reduced thickness with a decrease in pH and therefore represent valuable bioindicators to monitor the impacts of ocean acidification. Over the past decades, several studies have highlighted the striking diversity of shell microstructures in pteropods, with exceptional mechanical properties, but their evolution and future in acidified waters remains uncertain. Here, we revisit the body-of-work on pteropod biomineralization, focusing on shell microstructures and their evolution. The evolutionary history of pteropods was recently resolved, and thus it is timely to examine their shell microstructures in such context. We analyse new images of shells from fossils and recent species providing a comprehensive overview of their structural diversity. Pteropod shells are made of the crossed lamellar and prismatic microstructures common in molluscs, but also of curved nanofibers which are proposed to form a helical three-dimensional structure. Our analyses suggest that the curved fibres emerged before the split between coiled and uncoiled pteropods and that they form incomplete to multiple helical turns. The curved fibres are seen as an important trait in the adaptation to a planktonic lifestyle, giving maximum strength and flexibility to the pteropod thin and lightweight shells. Finally, we also elucidate on the candidate biomineralization genes underpinning the shell diversity in these important indicators of ocean health.